Gross, Microscopic and Ultra structural Pathology of Ocular Abnormalities in Farmed Halibut - David L Williams; W Mary Brancker (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
This report documents the gross pathological appearance, histopathology and ultra-structural studies of the ocular abnormalities previously reported in farmed Atlantic halibut  (Hippoglossus hippoglossus). 37% of eyes investigated were normal on gross and histopathological examination while 32% showed formation of an intraocular cyst in the choroid resulting in anterior movement of the retina. 27% showed scleral ectasia in which the posterior portion of the globe was enlarged, either generally or in a focal ectatic focus. In a small number of eyes the cystic posterior segment lesions contained fibrous and inflammatory tissue but most affected eyes showed cystic structures filled with gas or fluid. Although morphology was somewhat compromised in the majority of samples, histopathological and electron microscopic ultrastructural examination showed an endothelial lining to these posterior segment cysts suggesting that they have developed following gas bubble formation in vessels of the choroidal rete. This finding concurs with our previous research showing increased intraocular oxygen concentrations in the eyes of affected fish and suggests that the pathology seen here is predominantly associated with the formation of oxygen bubbles in the countercurrent multiplier system of the choroidal rete.